Intra-Religious Rivalry on Hadith Exposition in Ilorin Emirate, Nigeria - Adeyemi, Waliyullahi Adeola; Olayinka , AbdulRahman AbdulGafar (Jurnal Usuluddin, 2025)
Divergent views on Hadith exposition had been in existence since the Prophetic era. However, the Prophet resolved a myriad of theological and juristic differences among his Companions. The later generation experienced accretions due to strange ideology and sectarianism. Ilorin emirate Muslims had a similar experience of factionalism arising from divergent approaches to Hadith corpuses. The study explores the stages of Hadith development in Ilorin, consequences of intra-religious rivalry among Muslims and approach of the Ilorin Muslim factions to Hadith interpretation. The article appraises four selected Hadiths relating to theological and juristic polemics to curtail sectarian intolerance arising from the emirate. The article adopts an analytical method to unravel the polemics and relies on archive materials and oral interview for data collection and discussion. The article reveals that indoctrination of young scholars in Ilorin emirate had significantly influenced their Hadith exposition. Experts in the field of Hadith and Muslim preachers are enjoined to avoid sentiments in Hadith analysis.